Hubungan status gizi dengan pertumbuhan dan perkembangan balita 1-3 tahun - Setiawati Setiawati; Erna Rahma Yani; Megah Rachmawati (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Relationships between physical growth, mental development and nutritional status in children 1–3 years of ageBackground: Based on health surveys under the Ministry of Health of the Republic of Indonesia in 2018, the prevalence of delayed gross motor development, social personal, soft motor and language development in children aged 0.5 - 5.9 years is still high reaching 11.5%, up to 21, 6%, and the prevalence of malnutrition reaches 3.9%. The percentage of malnutrition in Lampung Province is 1.6% to 12.4%.Purpose: Knowing relationships between physical growth, mental development and nutritional status in children 1–3 years of age.Method: A quantitative research, using a cross-sectional approach with a population was mothers of children aged 1-3 years at the Palapa Health Center in Bandar Lampung City with a sample of 203 toddlers, using random sampling with proportional random sampling technique. Data collection techniques were used by observing toddlers and filling in the Pre-Screening Questionnaire of Development (KPSP) by their mothers. The statistical test used was the Chi Square test.Results: The frequency distribution of toddlers with adequate nutrition status of 104 toddlers (51.2%), appropriate in physical growth as many as 134 toddlers (66.0%), and appropriate in mental development was 142 toddlers (70.0%). There is a relationship of nutritional status with the physical growth (p value 0.001, OR 2.8).There is a relationship of nutritional status with the mental development (p value 0.007, OR 2.4)Conclusion: There is a relationships between physical growth, mental development and nutritional status in children 1–3 years of age. Suggestions for health workers are expected to further improve the monitoring of the nutritional status of children and conduct routine early detection of deviations of child developmentKeywords: Physical growth; Mental development; Nutritional status; Children 1–3 years of agePendahuluan: Berdasarkan survey kesehatan dibawah Kementerian Kesehatan Republik Indonesia tahun 2018, prevalensi keterlambatan perkembangan motorik kasar, sosial personal, motorik halus dan perkembangan bahasa pada anak usia 0,5 – 5,9 tahun masih tinggi mencapai 11,5 %, sampai dengan 21,6%, dan prevalensi gizi buruk hingga mencapai 3,9%. Provinsi Lampung persentase gizi buruk sebesar 1,6%, dan gizi kurang 12,4%.Tujuan: Diketahui hubungan status gizi dengan pertumbuhan dan perkembangan balita 1-3 tahun di Puskesmas Palapa Kota Bandar Lampung tahun 2019.Metode: Penelitian kuantitatif, menggunakan pendekatan cross sectional dengan populasi dalam para ibu yang mempunyai balita 1-3 tahun di Puskesmas Palapa Kota Bandar Lampung dengan sampel 203 balita, menggunakan random sampling dengan teknik Proportional random sampling. Tehnik pengumpulan data menggunakan dengan cara mengobservasi balita dan pengisian data kuesioner KPSP oleh ibu yang mempunyai balita yang dijadikan sebagai responden . Uji statistik yang digunakan adalah uji Chi Square.Hasil: Distribusi frekuensi balita dengan asupan gizi cukup yaitu sebanyak 104 balita (51,2%), pertumbuhan kotegori sesuai sebanyak 134 balita (66,0%), perkembangan yang kategori tidak menyimpang sebanyak 142 balita (70,0%). Ada hubungan status gizi dengan pertumbuhan balita 1-3 tahun (p value 0,001, OR 2,8) Ada hubungan status gizi dengan perkembangan balita 1-3 tahun (p value 0,007, OR 2,4)Simpulan: Adanya hubungan status gizi dengan pertumbuhan dan perkembangan balita 1-3 tahun di Puskesmas Palapa Kota Bandar Lampung tahun 2019. Saran bagi tenaga kesehatan diharapkan lebih meningkatkan lagi pemantauan terhadap status gizi anak dan melakukan deteksi dini secara rutin terhadap penyimpangan perkembangan anak.